2003
DOI: 10.1034/j.1399-3046.2003.02048.x
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin treatment for hyperlipidemia in pediatric renal transplant recipients

Abstract: The objective of this prospective study was to determine the prevalence of hyperlipidemia in our pediatric renal transplant patients and to treat those with persistently elevated cholesterol and/or low-density lipoprotein (LDL) levels. All patients with a functioning renal allograft for greater than 6 months were studied (n = 18). Patients with cholesterol and/or LDL levels greater than the 95th percentile (n = 9) were commenced on an HMG-CoA reductase inhibitor, Atorvastatin and monitoring was performed for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 27 publications
1
13
1
Order By: Relevance
“…Only limited data are available regarding the safe use of statins in pediatric renal patients, including transplant recipients, and any published studies so far have only included lowdose statins. For example, Argent et al [22] studied a cohort of 18 renal transplant patients prescribed a low-dose atorvastatin (5 mg for patients weighing \50, 10 mg for those weighing [50 kg). Another complicating factor for patients with renal disease is the potential for compromised glomerular filtration rates.…”
Section: Discussionmentioning
confidence: 99%
“…Only limited data are available regarding the safe use of statins in pediatric renal patients, including transplant recipients, and any published studies so far have only included lowdose statins. For example, Argent et al [22] studied a cohort of 18 renal transplant patients prescribed a low-dose atorvastatin (5 mg for patients weighing \50, 10 mg for those weighing [50 kg). Another complicating factor for patients with renal disease is the potential for compromised glomerular filtration rates.…”
Section: Discussionmentioning
confidence: 99%
“…[76] The use of HMG-CoA reductase inhibitors (statins), particularly pravastatin and atorvastatin, has been shown to be safe and effective in pediatric kidney and heart transplant recipients. [80][81][82] …”
Section: Dyslipidemiamentioning
confidence: 98%
“…Atorvastatin (in low doses, 2.5 mg to 10 mg/day) produced a reduction in TC levels by 32%-41%, in LDL-C levels by 42%-57%, while one study showed a decrease in apo B concentration by 29.5% and the other in TG levels by 44% [209,210]. No adverse events were reported in any study.…”
Section: Statins In Paediatric and Adolescent Transplant Recipientsmentioning
confidence: 72%
“…Two statins that have been evaluated in renal transplant patients are atorvastatin and pravastatin [208][209][210][211]. Atorvastatin (in low doses, 2.5 mg to 10 mg/day) produced a reduction in TC levels by 32%-41%, in LDL-C levels by 42%-57%, while one study showed a decrease in apo B concentration by 29.5% and the other in TG levels by 44% [209,210].…”
Section: Statins In Paediatric and Adolescent Transplant Recipientsmentioning
confidence: 98%